Comparison of injury patterns among highly specialized athletes in individual, team, and repetitive motion team sports - McLoughlin, D. E.; Kwon, S.; Bajaj, P. M.; Sandoval, L.; Murday, P. F.; Burgess, J. K.; Labella, C. R. (The Physician and Sportsmedicine, 2025)
Objective Overuse injuries are more associated with highly specialized youth athletes in individual sports than those in team sports; however, as baseball, softball, and volleyball involve frequent repetitive motions, these repetitive motion team sports (RMTS) may see a greater proportion of overuse injuries than non-repetitive motion team sports (non-RMTS). The objective of the present study is to compare the distribution of injuries (overuse vs. acute) in RMTS to non-RMTS and individual sports among highly specialized youth athletes.